Prolonged Labor and Gestational Age, with the Incidence of NeonatProlonged Labor and Gestational Age, with the Incidence of Neonatorum Asphyxia in Newborns in the Perinatology Unit of Guido Valadares National Hospitalorum Asphyxia in Newborns in the Perinatology Unit of Guido Valadares National Hospital - da Conceição, José Ximenes; Rakhmawat, Windy; Suzana Mediani, Henny; Mediawati, Ati Surya; Fatima Cabral, Cenia (Rifa'Institute, 2026)
Introduction: Neonatal asphyxia—defined as failure to establish adequate breathing at birth—remains a major cause of neonatal morbidity and mortality, especially in developing countries. Prolonged labour and abnormal gestational age can impair placental oxygen transfer and heighten asphyxia risk. Objective: To examine the association between prolonged labour, gestational age, and neonatal asphyxia among newborns treated in the Perinatology Unit of Guido Valadares National Hospital. Method: A cross-sectional correlational study involved 85 mother–infant pairs selected purposively from 110 admissions in 2025. Prolonged labour and gestational age were independent variables; neonatal asphyxia was the outcome. Data were gathered via structured questionnaire and medical records, then analysed with multinomial regression (α = 0.05). Results and Discussion: Prolonged labour showed a significant independent association with asphyxia (p = 0.001), whereas gestational age alone did not (p = 0.389). Simultaneous analysis demonstrated that both variables together were significantly related to asphyxia incidence (p = 0.005). Conclusion: Prolonged labour is the principal contributor to neonatal asphyxia, and its combined effect with gestational age further elevates risk. Rigorous intrapartum monitoring and timely obstetric intervention are essential to improve neonatal outcomes